2022
DOI: 10.1002/jsfa.12028
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic stimulation of milk fermentation: effects on degradation of pesticides and physiochemical, antioxidant, and flavor properties of yogurt

Abstract: BACKGROUND Ultrasound has the potential to increase microbial metabolic activity, so this study explored the stimulatory effect of ultrasound pre‐treatment on the degradation of four common pesticides (fenitrothion, chlorpyrifos, profenofos, and dimethoate) during milk fermentation by Lactobacillus plantarum and its effect on yogurt quality. RESULTS Appropriate ultrasound pretreatment significantly enhanced the growth of L. plantarum. The degradation percentages of pesticides increased by 19–38% under ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…(2020) reported that the lactic acid value in yoghurts produced after ultrasound application to milk was similar to the control group, while Yuan et al. (2022) reported that acetic acid was higher in control group samples. Nguyen et al.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…(2020) reported that the lactic acid value in yoghurts produced after ultrasound application to milk was similar to the control group, while Yuan et al. (2022) reported that acetic acid was higher in control group samples. Nguyen et al.…”
Section: Resultsmentioning
confidence: 91%
“…In addition to being a dairy product consumed all over the world with its unique nutritional elements, yoghurt is a functional food in terms of human health with the biochemical compounds it contains (Yuan et al. 2022). In many studies conducted in recent years, it has been reported that regular intake of yoghurt and yoghurt bacteria (LAB) and their metabolites reduces obesity, diabetes, inflammation and blood cholesterol, and that yoghurt has anti‐carcinogenic, anti‐oxidative and immunomodulatory effects (Mousavi et al.…”
Section: Introductionmentioning
confidence: 99%
“…The residual profenofos and degradation products were extracted using the Quick Easy Cheap Effective Rugged and Safe (QuEChERS) method, as described in our previous study . After extraction, the supernatant was filtered through a 0.22 μm nylon filter (Whatman, Germany) before gas chromatography–mass spectrometry (GC–MS) analysis.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The residual profenofos and degradation products were extracted using the Quick Easy Cheap Effective Rugged and Safe (QuEChERS) method, as described in our previous study. 13 After extraction, the supernatant was filtered through a 0.22 μm nylon filter (Whatman, Germany) before gas chromatography−mass spectrometry (GC−MS) analysis. A Shimadzu 2010 GC−MS system (Shimadzu, Japan) equipped with a DB-1701 column (30 m × 0.32 mm i.d., 1.0 μm, Agilent, USA) was used to detect profenofos and degradation products.…”
Section: Determination Of Residual Profenofos and Degradation Productsmentioning
confidence: 99%
See 1 more Smart Citation